2016
DOI: 10.18239/ocnos_2016.15.1.941
|View full text |Cite
|
Sign up to set email alerts
|

Mejora en la motivación por la Lectura Académica: la mirada de estudiantes motivados

Abstract: Dada la importancia de la lectura académica en la formación universitaria y que uno de los factores gravitantes en este tipo de tarea son los aspectos motivacionales, el presente trabajo tuvo como objetivo identificar los elementos, que según los propios protagonistas explicarían el incremento de su motivación por la lectura de textos académicos. El estudio de carácter mixto se realizó en dos fases. En una primera fase, de corte cuantitativo, fueron identificados a partir de una muestra amplia (n=1205) estudia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
20

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
0
8
0
20
Order By: Relevance
“…Academic texts and motivation to read them fit well within the expectancy-value model (Anmarkrud & Brâten, 2009;Muñoz et al, 2016). Observing feelings of competence in students and analysing value attributed to tasks based on interest and attainment, perception of utility and the cost students are willing to assume provides interesting clues to be able to intervene and promote these dimensions (cf.…”
Section: Motivation As a Results Of The Expectancy And Value Of The Taskmentioning
confidence: 87%
See 2 more Smart Citations
“…Academic texts and motivation to read them fit well within the expectancy-value model (Anmarkrud & Brâten, 2009;Muñoz et al, 2016). Observing feelings of competence in students and analysing value attributed to tasks based on interest and attainment, perception of utility and the cost students are willing to assume provides interesting clues to be able to intervene and promote these dimensions (cf.…”
Section: Motivation As a Results Of The Expectancy And Value Of The Taskmentioning
confidence: 87%
“…Observing feelings of competence in students and analysing value attributed to tasks based on interest and attainment, perception of utility and the cost students are willing to assume provides interesting clues to be able to intervene and promote these dimensions (cf. Muñoz et al, 2016).…”
Section: Motivation As a Results Of The Expectancy And Value Of The Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, having confirmed a model for engagement within professional training programmes for future teachers, we note that many of these motivational variables are modifiable through educational interventions. The literature discusses evidence in this sense regarding, for example, motivation to teach (Whitaker & Valtierra, 2018); or academic reading motivation, especially the value assigned to this activity (Muñoz et al, 2016). Other interventions in these variables may also be designed to increase student engagement with the opportunities provided by teachertraining programmes.…”
Section: Sexmentioning
confidence: 99%
“…In turn, when students are highly motivated in these areas, we may expect better performance when working as teachers (Tang, Wong, & Cheng, 2015). Next, Academic Reading Motivation (De Naeghel et al, 2012;Muñoz, Valenzuela, Avendaño, & Núñez, 2016), has been shown to be essential to be able to adopt and explore content. Studies have shown that this variable is essential to encourage students to explore text-based content which is primarily mediated by specialized literature in the discipline (e.g., pedagogy, psychology) (Watkins & Coffey, 2004).…”
mentioning
confidence: 99%